Efficacy and tolerability of a cream containing modified glutathione (GSH‐C4), beta‐Glycyrrhetic, and azelaic acids in mild‐to‐moderate rosacea: A pilot, assessor‐blinded, VISIA and ANTERA 3‐D analysis, two‐center study (The "Rosazel" Trial). (21st September 2020) - Dall'Oglio, Federica; Puviani, Mario; Milani, Massimo; Micali, Giuseppe
Abstract: Background: Rosacea is a very common, chronic inflammatory disease characterized by flushing, erythema and inflammatory lesions. Increased oxidative stress plays a relevant pathogenetic role in Rosacea. Intracellular Glutathione (GSH) is the main scavenger protective mechanism against increased oxidative stress. An altered GSH metabolism in Rosacea has been described. GSH‐C4 is a modified GSH molecule characterized by a better intracellular bioavailability and longer half‐life. A daily cream (E‐AR) containing GSH‐C4 (0.1%) with beta‐Glycyrrhetic (0.5%) and azelaic acids (10%), with an SPF of 30, is available. Aim: In a pilot, prospective, two‐center, assessor‐blinded study we evaluate the efficacy and the tolerability of E‐AR cream in subjects with mild to moderate Rosacea treated for 8 weeks. Patients and Methods: The main outcomes were the Investigator Global Assessment (IGA) 7‐point score (from 0, completely clear; to 6, severe) and the clinical and instrumental erythema severity score (ESS) (from 0 to 4) evaluated in a blinded fashion (randomly coded photographs) at baseline, after 4 (only clinical) and 8 weeks (clinical and instrumental). VISIA evaluation for erythema and lesion counts and ANTERA 3D analysis for skin haemoglobin concentration (a parameter associated with inflammation) were also performed at the same time points. Analysis of primary outcomes was performed on an intention‐to‐treat basis. Tolerability was evaluated at week 4 and 8 recording spontaneously reported side effects. Results: Thirty subjects (22 women and 8 men; mean age 38 years) were enrolled after their written informed consent. Twenty‐six (87%) subjects completed the study phases. Four subjects stopped prematurely the trial due to low skin tolerability (n=3) or lost to follow‐up (n=1). At baseline, mean (SD) IGA score was 2.6 (0.9). At week 4, IGA score decreased (NS) to 2.3 (1.2). IGA score decreased significantly (p=0.0001) at week 8 to 1.2 (1) (mean difference 1.3; 95% CI of the difference from 0.9 to 1.7) in comparison with the baseline. The inflammatory mean (SD) lesion count, evaluated clinically, were 5.1(2.5) at baseline, 2.8 (1.9) at week 4, and 1.9 (1.7) at week 8 ( P =0.0001; ANOVA Test), representing a 63% reduction. This reduction was confirmed by inflammatory lesions count performed on VISIA pictures (from 4.5 at baseline to 1.7 lesions at week 8). Similar evolution was observed for the clinical and instrumental ESS with a reduction of 56% (clinical) and 48% (VISIA), respectively, at week 8 in comparison with the baseline. ANTERA 3D photographs confirmed the positive evolution observed clinically with a significant reduction (‐24%) in hemoglobin content: from 1.88 at baseline to 1.44 at week 8. Conclusion: This new GSH‐C4, beta‐glycyrrethic and azelaic acids cream has shown to be efficacious in mild to moderate rosacea subjects. Local tolerability is in line with other anti‐rosacea treatments.